2020
DOI: 10.1016/j.ultsonch.2020.105123
|View full text |Cite
|
Sign up to set email alerts
|

Sonophotocatalytic degradation of sodium diclofenac using low power ultrasound and micro sized TiO2

Abstract: The nonsteroidal anti-inflammatory drug sodium diclofenac (DC) is an emerging water pollutant which resists conventional wastewater treatments. Here the sonophotocatalytic degradation of DC was carried out using micrometric TiO2 (both pristine and Ag-decorated), UV-A irradiation and 20 kHz pulsed ultrasound. Sonophotocatalytic tests were compared with photolysis, sonolysis, sonophotolysis, sonocatalysis and photocatalysis data performed in the same conditions. A synergy index of over 2 was determined for tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 68 publications
(69 reference statements)
4
37
1
Order By: Relevance
“…However, TiO 2 presents several disadvantages. For instance, our recent investigation on sonophotocatalytic degradation of DCF by micro-sized TiO 2 revealed the crucial role of the water medium, showing a decrease in performance of the photocatalyst in terms of DCF abatement, number of by-products formed and their degradation, when drinking water is used instead of ultrapure water [9] .…”
mentioning
confidence: 99%
“…However, TiO 2 presents several disadvantages. For instance, our recent investigation on sonophotocatalytic degradation of DCF by micro-sized TiO 2 revealed the crucial role of the water medium, showing a decrease in performance of the photocatalyst in terms of DCF abatement, number of by-products formed and their degradation, when drinking water is used instead of ultrapure water [9] .…”
mentioning
confidence: 99%
“…Few investigations have reported on pilot scale reactors [51,58] and most of these studies have employed slurry based photo-reactors [59][60][61]. Moreover, numerous studies on reactor configurations focus merely on the main pollutant disappearance, without providing information on the reaction intermediates, which oftentimes are still toxic and poorly biodegradable compounds [62]. The evaluation of the long-term performance of the photocatalytic systems is also another scantly investigated point, as most studies report, at best, a few photocatalytic consecutive tests.…”
Section: Figurementioning
confidence: 99%
“…The occurrence of organic or inorganic species other than the main pollutant may inhibit the photocatalytic degradation or requires additional amounts of catalyst [65]. Moreover, photocatalysts can exhibit largely different response to complex water matrices [62], which underscores the limited value of comparisons of photocatalytic activity in ultrapure water. Some inorganic electrolytes, such as bicarbonates and chlorides, can have a detrimental effect on the photocatalytic activity by acting as radical scavengers [28].…”
Section: Presence Of Interfering Species and Real Water Matricesmentioning
confidence: 99%
“…[41] Meroni et al sonophotocatalytically degraded over 80 % diclofenac in drinking water using a micro-metric TiO 2 catalyst. [42] Schieppati et al implemented a sonophotocatalytic degradation of an herbicidal pollutant and degraded 100 % of it in about 3 h. [43] Khani et al reported the sonophotocatalytic degradation of APAP and AMO over Mn-TiO 2 systems with tuned band-gap and reached over 25 % and 50 % conversion, respectively, under UV light. [44] Only one recent paper reported the oxidation of AMO based on ultrasound and ozone: [45] the authors treated AMO by medium-high frequency ultrasound irradiation and/or ozonation; they applied ultrasonic power at 75 W, changing the frequency and obtaining a maximum AMO removal of 99 %, but with 10 % of mineralization only.…”
Section: Introductionmentioning
confidence: 99%
“…Meroni et al. sonophotocatalytically degraded over 80 % diclofenac in drinking water using a micro‐metric TiO 2 catalyst [42] . Schieppati et al.…”
Section: Introductionmentioning
confidence: 99%